Pembelajaran Sejarah Indonesia di SMAN 1 Malang dalam Mengembangkan Kemampuan Berpikir Historis - Siti Faizatun Nisa'; Joko Sayono; Indah Wahyu Puji Utami (Universitas Negeri Malang, 2019)
Indonesian history learning curriculum hopes student historical thinking ability can be developed after the learning occured. Discussion focus of this article is history learning process in SMA N 1 Malang and student historical thinking ability. This research uses qualitative descriptive method. Research process is done by looking for data about research focus. The gotten data then explained and analyzed to explain research focus. Conclusion in this research is history learning in SMA N 1 Malang is in accordance with the valid curriculum. History learning that occures also able to develop student historical thinking ability. Through research instrument that is modified from Seixas’s six hisrorical thinking component, it is known that student able to think historically. DOI: http://dx.doi.org/10.17977/um033v2i22019p202